Inhibition of citrate cotransporter Slc13a5/mINDY by RNAi improves hepatic insulin sensitivity and prevents diet-induced non-alcoholic fatty liver disease in mice - Sebastian Brachs; Angelika F. Winkel; Hui Tang; Andreas L. Birkenfeld; Bodo Brunner; Kerstin Jahn-Hofmann; Daniel Margerie; Hartmut Ruetten; Dieter Schmoll; Joachim Spranger (Elsevier, 2016)
Objective: Non-alcoholic fatty liver disease is a world-wide health concern and risk factor for cardio-metabolic diseases. Citrate uptake modifies intracellular hepatic energy metabolism and is controlled by the conserved sodium-dicarboxylate cotransporter solute carrier family 13 member 5 (SLC13A5, mammalian homolog of INDY: mINDY). In Drosophila melanogaster and Caenorhabditis elegans INDY reduction decreased whole-body lipid accumulation. Genetic deletion of Slc13a5 in mice protected from diet-induced adiposity and insulin resistance. We hypothesized that inducible hepatic mINDY inhibition should prevent the development of fatty liver and hepatic insulin resistance. Methods: Adult C57BL/6J mice were fed a Western diet (60% kcal from fat, 21% kcal from carbohydrate) ad libitum. Knockdown of mINDY was induced by weekly injection of a chemically modified, liver-selective siRNA for 8 weeks. Mice were metabolically characterized and the effect of mINDY suppression on glucose tolerance as well as insulin sensitivity was assessed with an ipGTT and a hyperinsulinemic-euglycemic clamp. Hepatic lipid accumulation was determined by biochemical measurements and histochemistry. Results: Within the 8 week intervention, hepatic mINDY expression was suppressed by a liver-selective siRNA by over 60%. mINDY knockdown improved hepatic insulin sensitivity (i.e. insulin-induced suppression of endogenous glucose production) of C57BL/6J mice in the hyperinsulinemic-euglycemic clamp. Moreover, the siRNA-mediated mINDY inhibition prevented neutral lipid storage and triglyceride accumulation in the liver, while we found no effect on body weight. Conclusions: We show that inducible mINDY inhibition improved hepatic insulin sensitivity and prevented diet-induced non-alcoholic fatty liver disease in adult C57BL6/J mice. These effects did not depend on changes of body weight or body composition. Keywords: INDY/Slc13a5, siRNA, Insulin resistance, Steatosis, Citrate transport, Lipid accumulation